2014
DOI: 10.1089/jwh.2013.4535
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Awareness and Outcomes During Acute Traumatic Brain Injury Recovery

Abstract: Background: Recent literature on traumatic brain injury (TBI), though mixed when reporting outcomes, seems collectively to suggest possible gender advantage for women in postinjury recovery, especially in executive functions. Hormonal neuroprotection, through female reproductive hormones, is often proposed as an underlying factor in these results. We explored potential gender differences in an aspect of executive functions, selfawareness (SA), which is often impaired after TBI, limits patient effort in critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 64 publications
0
29
1
1
Order By: Relevance
“…Of particular note is that women and men had no differences in long-term outcomes after TBI across the three time points. The anecdotal observations from clinical practice that women tend to experience better outcomes than men after TBI, as well as findings from the US examining functioning during discharge from acute TBI (36) were not confirmed in this study. Our results are also not in line with number of studies that showed gender influence on TBI outcomes such as a metaanalysis of outcome studies from mild-to-severe TBI that found poorer outcomes in women for 85% of the measured variables, including disability and subjective symptoms (37).…”
Section: Discussioncontrasting
confidence: 79%
“…Of particular note is that women and men had no differences in long-term outcomes after TBI across the three time points. The anecdotal observations from clinical practice that women tend to experience better outcomes than men after TBI, as well as findings from the US examining functioning during discharge from acute TBI (36) were not confirmed in this study. Our results are also not in line with number of studies that showed gender influence on TBI outcomes such as a metaanalysis of outcome studies from mild-to-severe TBI that found poorer outcomes in women for 85% of the measured variables, including disability and subjective symptoms (37).…”
Section: Discussioncontrasting
confidence: 79%
“…Controlled animal experiments have shown better cognitive outcomes among females after mild TBI (Bramlett and Dietrich, 2001 ; O’Connor et al, 2003 ; Bazarian et al, 2010 ). Evidence from a human study also finds that women have superior executive functioning when compared with men after acute TBI (Niemeier et al, 2014 ). Other studies show that women outperform men in the tasks of verbal memory and learning measures following TBI (Farace and Alves, 2000 ; Covassin et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research ndings have been strikingly consistent in showing that men and women have different health-related behaviours (e.g. [39]). For instance, men, as a group, are more likely to avoid seeking help for physical and mental health problems, due to a gender-role con ict (see [40] for a review).…”
Section: Discussionmentioning
confidence: 77%